2016
DOI: 10.1074/jbc.m116.716704
|View full text |Cite
|
Sign up to set email alerts
|

Rifampin Resistance Mutations Are Associated with Broad Chemical Remodeling of Mycobacterium tuberculosis

Abstract: Global control of tuberculosis has become increasingly complicated with the emergence of multidrug-resistant strains of Mycobacterium tuberculosis. First-line treatments are anchored by two antibiotics, rifampin and isoniazid. Most rifampin resistance occurs through the acquisition of missense mutations in the rifampin resistance-determining region, an 81-base pair region encoding the rifampin binding site on the ␤ subunit of RNA polymerase (rpoB). Although these mutations confer a survival advantage in the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 47 publications
5
42
1
Order By: Relevance
“…For instance, transcriptomic and proteomic analysis of Mtb clinical isolates containing rpoB mutations demonstrated upregulation of polyketide synthases, which are enzymes involved in the biosynthesis of phthiocerol dimycocerosate (PDIM) ( Bisson et al, 2012 ). More recently, lipidomic profiling of rpoB mutant Mtb showed altered concentrations of mycobactin siderophores and acylated sulfoglycolipids ( Lahiri et al, 2016 ), while metabolomics revealed decreased synthesis of various branched-chain fatty acids ( du Preez and Loots du, 2012 ). These cell wall-associated lipids, including PDIM, mycobactin, sulfoglycolipids, and fatty acids, have been implicated in cell wall permeability and virulence ( Camacho et al, 2001 ; Converse et al, 2003 ; Yeruva et al, 2006 ; Gebhardt et al, 2007 ; Gilmore et al, 2012 ; Reddy et al, 2013 ; Lahiri et al, 2016 ; Quigley et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, transcriptomic and proteomic analysis of Mtb clinical isolates containing rpoB mutations demonstrated upregulation of polyketide synthases, which are enzymes involved in the biosynthesis of phthiocerol dimycocerosate (PDIM) ( Bisson et al, 2012 ). More recently, lipidomic profiling of rpoB mutant Mtb showed altered concentrations of mycobactin siderophores and acylated sulfoglycolipids ( Lahiri et al, 2016 ), while metabolomics revealed decreased synthesis of various branched-chain fatty acids ( du Preez and Loots du, 2012 ). These cell wall-associated lipids, including PDIM, mycobactin, sulfoglycolipids, and fatty acids, have been implicated in cell wall permeability and virulence ( Camacho et al, 2001 ; Converse et al, 2003 ; Yeruva et al, 2006 ; Gebhardt et al, 2007 ; Gilmore et al, 2012 ; Reddy et al, 2013 ; Lahiri et al, 2016 ; Quigley et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…In Neisseria meningitidis and Staphylococcus aureus, rpoB mutations lead to a decrease permeability of the cell wall, which can be related to a subsequent increase in tolerance to certain antibiotics such as vancomycin [96][97][98]. Interestingly, after exposure to RIF, Mtb also appears to have an increased tolerance to ofloxacin, probably because of an increase activity of efflux pumps [99], although recent findings from our laboratory as well as others also suggest a potential role for cell permeability [75,100]. In our study, isogenic Mtb pairs with two different rpoB mutations and representing two different genetic lineages (Beijing and Haarlem) showed an increased abundance of proteins involved polyketide synthesis.…”
Section: Acquisition Of Rifampicin (Rif) Resistance In Isogenic Mtb Smentioning
confidence: 78%
“…The analysis revealed reduced levels of di-acylated sulfoglycolipid (Ac2SGL) and mycobactins (including carboxymycobactins), while increased levels of PDIM compared to their DS parental strain. These compounds were identified among 172 features in the W-Beijing group and 102 features in the CDC1551 group analyzed by high performance liquid chromatography (HPLC) mass quadrupole-time-of-flight (QTOF) MS and suggesting a global remodeling of the cell wall after acquisition of RIF resistance [100]. This study supports previous findings from our group, which included a significant increase of diacylglycerol phosphocholines and PDIM precursors as observed by ultra-performance liquid chromatography (UPLC)-QTOF [75].…”
Section: Lipidomics In Rifr Mtb Strainsmentioning
confidence: 99%
“…Using GC-MS on a small number of rpoB mutants, du Preez and Loots found decreased levels of 10-methyl branched-chain fatty acids and cell wall lipids, suggestive evidence of increased metabolism of short fatty acids [70,71]. Using LC-MS lipidomics, Lahiri et al reported altered levels of mycobactin siderophores and acylated sulfoglycolipids [72]. Mutations in catalase-peroxidase (katG) that render resistance to the frontline drug isoniazid, by preventing activation into its biochemically active form, were similarly associated with increased levels of several fatty acids, alcohols and alkanes [73].…”
Section: Compound-based Drug Developmentmentioning
confidence: 99%